2007
DOI: 10.1243/09544062jmes813ft
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of a two-dimensional Euler flow solver using commodity graphics hardware

Abstract: The implementation of a two-dimensional Euler solver on graphics hardware is described. The graphics processing unit is highly parallelized and uses a programming model that is well suited to flow computation. Results for a transonic turbine cascade test-case are presented. For large grids (106 nodes) a 40 times speed-up compared with a Fortran implementation on a contemporary CPU is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 9 publications
1
34
0
3
Order By: Relevance
“…This is shown in Figure 8, while the benchmarking hardware details are summarized in section 5.4.2. A 40x speed-up has been reported previously by the present authors [1] when comparing the same implementations, but running on a slower CPU. The large speed-up can be explained by the memory fetches performed by the solver having good 2D spatial locality, thereby making efficient use of the GPU's texture cache.…”
Section: Performancesupporting
confidence: 67%
See 1 more Smart Citation
“…This is shown in Figure 8, while the benchmarking hardware details are summarized in section 5.4.2. A 40x speed-up has been reported previously by the present authors [1] when comparing the same implementations, but running on a slower CPU. The large speed-up can be explained by the memory fetches performed by the solver having good 2D spatial locality, thereby making efficient use of the GPU's texture cache.…”
Section: Performancesupporting
confidence: 67%
“…The solutions presented are physically sensible and speed-ups compared to an equivalent CPU code of 10-20 times are reported. The present authors have recently published results from a 2D Euler solver [1] with speed-ups of up to 40 times obtained.…”
Section: Introductionmentioning
confidence: 99%
“…This situation has begun to improve with the recent release of the OpenCL standard, although this is not yet supported by all vendors. As an example of what may be possible, Brandvik and Pullan [37] implemented an Euler solver on a graphics processing unit (GPU) and reported speed-ups of up to 40 compared to a conventional Intel CPU. It remains to be seen if these impressive speed-ups can be maintained for a cluster of hundreds or thousands of GPUs when the issues of inter-GPU communication will become important.…”
Section: Parallelisationmentioning
confidence: 99%
“…To list a few of the CUDAaccelerated CFD applications, Elsen et al 11 reported a 3D high-order FDM solver for large calculation on multi-block structured grids; Klöckner et al 16 developed a 3D unstructured high-order nodal DGM solver for the Maxwell's equations; Corrigan et al 10 proposed a 3D FVM solver for compressible inviscid flows on unstructured tetrahedral grids; Zimmerman et al 29 presented an SDM solver for the Navier-Stokes equations on unstructured hexahedral grids; and more as in the references. 3,4,12,7,21,23,13,19,8,14,1,9 However applying CUDA to a legacy CFD code is not likely an easy job since the developer has to define an explicit layout of the threads on the GPU (numbers of blocks, numbers of threads) for each kernel function. 15 So what if the CFD code designers have to meet specific investment requirements like (1) enable GPU computing for legacy CFD programs at a minimum extra cost in time and effort (usually a major concern for large-scale code development), (2) enable the GPU-accelerated programs running on different platforms (similar to the situation that the video game designers would like to make their products available across platforms)?…”
Section: Introductionmentioning
confidence: 99%